1996
DOI: 10.1007/bf02347678
|View full text |Cite
|
Sign up to set email alerts
|

Root respiration rate before and just after clear‐felling in a mature, deciduous, broad‐leaved forest

Abstract: Soil respiration was measured throughout the year (June 1992 to May 1993) in a mature, deciduous, broad-leaved forest and an adjacent, clear-felled stand which was made in November 1991, in Hiroshima Prefecture, west Japan. The same soil temperature and soil moisture content as those in the forest stand were maintained in two frame boxes covered with sheers of white netting in the dear-felled stand to observe soil respiration. A herbicide was applied to the cut end of all stumps in one of the two frame boxes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 5 publications
11
60
4
Order By: Relevance
“…The strong seasonal variations of soil CO 2 efflux recorded in our study re-emphasize these controls by temperature and soil moisture as mentioned in previous studies in Mediterranean [4,10,12,15,32,38] or semi-arid conditions [17]. When soil water content remains constantly high, temperature is the only parameter related to soil respiration variations [28,30,46,47]. In the majority of the studies, soil moisture plays an important role and many functions have been proposed to describe it [11,49].…”
Section: Discussionsupporting
confidence: 88%
“…The strong seasonal variations of soil CO 2 efflux recorded in our study re-emphasize these controls by temperature and soil moisture as mentioned in previous studies in Mediterranean [4,10,12,15,32,38] or semi-arid conditions [17]. When soil water content remains constantly high, temperature is the only parameter related to soil respiration variations [28,30,46,47]. In the majority of the studies, soil moisture plays an important role and many functions have been proposed to describe it [11,49].…”
Section: Discussionsupporting
confidence: 88%
“…Our results suggest that about 40% of the soil CO 2 -C efflux can be attributed directly to root respiration, a value that closely corresponds to the biome-wide average of 41% for temperate deciduous forests (Gower 2003). A wide range in this percentage has been reported by different forest studies, due in part to methodological differences, but root respiration probably comprises roughly half of TSR in many forests (Nakane et al 1996;Hanson et al 2000). Not surprisingly, the proportion of soil respiration attributed to roots is higher for the mineral soil (45%) than the forest floor (35%) at the HBEF because of the large annual input of labile organic matter to the forest floor in litterfall.…”
Section: Heterotrophic Fluxessupporting
confidence: 67%
“…The regression equation was derived and soil respiration was calculated by performing regression analysis on the measured soil respiration and soil temperature. According to existing studies, the contribution of root respiration towards the soil respiration was 49% in the Pinus densiflora forest (Nakane et al 1983), 51% in the Quercus serrata forest (Nakane et al 1996), 46% in the Pinus koraiensis plantation (Pyo et al 2003), 31% in the Quercus dominant forest (Lee et al 2010), and 34% in the Quercus acutissima forest . In this study, the root respiration was estimated at 45% of the soil respiration based on the study of Wang et al (2012) who reported that the contribution of heterotrophic respiration towards the soil respiration of Q. glauca was 55%.…”
Section: Soil Respirationmentioning
confidence: 99%